2017
DOI: 10.1159/000450914
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Soluble Adenylyl Cyclase in Primary Biliary Cholangitis

Abstract: Background: Primary biliary cholangitis (PBC; previously referred to as primary biliary cirrhosis) is a chronic fibrosing cholangiopathy with the signature of an autoimmune disease and features of intrahepatic cholestasis. Immunosuppressing treatments are largely unsuccessful. Responsiveness to ursodeoxycholic acid and reduced expression of anion exchanger 2 (AE2) on canalicular membranes and small bile ducts underline the importance of bicarbonate transportation in its disease mechanism. Soluble adenylyl cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition to several studies indicating that AE2 was reduced in PBC, a recent study reported that downregulation of AE2 may sensitize BECs to apoptotic insults activating soluble adenylyl cyclase (sAC) [ 39 ]. sAC, an evolutionarily conserved bicarbonate sensor, plays a key role in regulating bile salt-induced apoptosis [ 42 ]. Reduced AE2 expression leads to a decrease in the bicarbonate secretion and bicarbonate accumulation in the cells.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%
“…In addition to several studies indicating that AE2 was reduced in PBC, a recent study reported that downregulation of AE2 may sensitize BECs to apoptotic insults activating soluble adenylyl cyclase (sAC) [ 39 ]. sAC, an evolutionarily conserved bicarbonate sensor, plays a key role in regulating bile salt-induced apoptosis [ 42 ]. Reduced AE2 expression leads to a decrease in the bicarbonate secretion and bicarbonate accumulation in the cells.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%
“…sAC has been shown to play a role in a number of physiological processes (Buffone, Wertheimer, Visconti, & Krapf, 2014; Chang, Beuers, & Oude Elferink, 2017; Desman, Waintraub, & Zippin, 2014; Ladilov & Appukuttan, 2014; Lee, Marmorstein, & Marmorstein, 2014; Levin & Buck, 2015; Muller, 2016; Schmid, Meili, & Salathe, 2014; Shim, Kim, & Ju, 2017; Stiles, Kapiloff, & Goldberg, 2014; Valsecchi, Konrad, & Manfredi, 2014). A number of sAC’s physiological roles have been identified genetically, via phenotypes observed in genetically engineered mice (Table 2).…”
Section: Physiological Roles Of Sac Identified Using Sac Inhibitorsmentioning
confidence: 99%
“…Bile acid exposure activates sAC causing downstream cytochrome c release and apoptosis, which can be prevented by sAC inhibition. These findings provide insight into the promising role of sAC in the pathogenesis of PBC [124].…”
Section: Acid-base Sensors In the Hepatobiliary Tractmentioning
confidence: 74%